Answer:
1) -184
2) 13
-3(
)+4
Explanation:
For problem number 1, Let's start by substituting all the x's for -3
So the equation will look like
p(-3)=
-
+7(-3)-10
Now, lets simplify by solving the exponents
First we'll do
which equals -27
Now we'll do
which equals 9
So now our equation looks like
p(-3)=4(-27)-5(9)+7(-3)-10
Now, we are going to multiply all these numbers
First 4(-27) which equals -108
Now -5(9) which equals -45
And finally 7(-3) which equals -21
Now our equation looks like
p(-3)= -108-45-21-10
Now we can solve
-108-45-21-10=-184